Silica composite material, preparation method thereof, secondary battery and electric device
Patent Information
- Application Number
- CN202380061326.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-28
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-04-28
AI Technical Summary
Existing silicon-based anode materials have large volume changes during the insertion and extraction of lithium ions, resulting in short cycle life, low rate performance, and poor conductivity, which limits the performance improvement of secondary batteries.
Using silicon-oxygen composite materials, by distributing first doping elements with high lithium ion diffusion coefficients, such as Sn, Ge, Sb, and Bi, in the silicon-oxygen material matrix, crystals smaller than 9nm are formed, which improves the lithium ion diffusion coefficient and alleviates silicon agglomeration. The clusters expand, enhancing structural integrity and coating the surface with a carbon layer, improving conductivity.
It extends the discharge time and cycle life of the battery, improves the rate performance and cycle performance, and enhances the structural stability and conductivity of the battery.
Smart Images

Figure CN119744455A_ABST
Abstract
Description
Silicon-oxygen composite material, preparation method thereof, secondary battery and electrical device Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a silicon-oxygen composite material, a preparation method thereof, a secondary battery, and an electrical device. Background Art
[0002] Secondary batteries, with their high capacity and long lifespan, are widely used in electronic devices such as mobile phones, laptops, electric bicycles, electric cars, electric airplanes, electric boats, electric toy cars, electric toy boats, electric toy airplanes, and power tools. Due to the significant progress made in secondary batteries, higher performance requirements have been placed on them. To increase the energy density of secondary batteries, the industry is currently considering the use of silicon-based negative electrode active materials. However, these materials exhibit inherent shortcomings, such as large expansion and poor conductivity, which severely impact the battery's cycle and rate performance, significantly limiting their further application.
[0003] Summary of the Invention
[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a silicon-oxygen composite material, which can be used as a negative electrode active material to prolong the discharge time of the battery, improve the battery's rate performance, extend the battery's cycle life, and improve the battery's cycle performance.
[0005] In a first aspect of the present application, a silicon-oxygen composite material is provided, which comprises a silicon-oxygen material matrix and a first doping element distributed in the silicon-oxygen material matrix, at least a portion of the first doping element exists in a crystalline form in the silicon-oxygen material matrix, and the grain size of the first doping element is ≤9 nm, wherein the first doping element satisfies: the lithium ion diffusion coefficient of the first doping element at 25°C is greater than the lithium ion diffusion coefficient of silicon at 25°C.
[0006] The first doping element is distributed in the form of crystals within the silicon oxide material matrix, and the grain size is less than or equal to 9 nm, indicating that the first doping element is uniformly dispersed in the silicon oxide material matrix at the atomic scale, which can effectively reduce the migration energy barrier of lithium ions, increase the lithium ion diffusion coefficient, improve the lithium ion migration kinetics, extend the discharge time of the battery, and improve the battery rate performance. In addition, the crystals formed by the first doping element are dispersed around the silicon grains, which can alleviate the growth of silicon clusters, effectively inhibit the expansion and pulverization effect of the silicon oxide composite material, enhance the structural integrity and volume stability of the silicon oxide composite material during the lithium insertion / extraction process, and improve the cycle performance of the battery. In addition, the first doping element exists in the form of crystals with small grain size, which will not cause major changes in the crystal structure of the silicon oxide material matrix, will not cause major changes in the phase properties of the material, can well maintain the structural stability of the material, is not easy to pulverize during the charge and discharge process, extends the cycle life of the battery, and improves the cycle performance of the battery.
[0007] In any embodiment, the lithium ion diffusion coefficient of the first doping element at 25°C is greater than 10 -14 cm 2 / S, can be greater than 10 -14 cm 2 / S and less than or equal to 10 -13 cm 2 / S.
[0008] In any embodiment, the lithium ion diffusion coefficient of silicon at 25°C is less than 10 - 14 cm 2 / S, can be greater than 10 -15 cm 2 / S and less than 10 -14 cm 2 / S.
[0009] In any embodiment, the first doping element includes at least one of Sn, Ge, Sb, Bi, and Sr.
[0010] The first doping element has an excellent lithium ion diffusion coefficient, and the raw materials are abundant and easily available. It is suitable for various batteries and has excellent application prospects.
[0011] In any embodiment, the grain size of the first doping element is ≤ 7 nm.
[0012] Controlling the grain size of the first doping element within a suitable range can further extend the discharge time of the battery, further improve the rate performance and cycle performance of the battery, and extend the cycle life of the battery.
[0013] In any embodiment, the XRD diffraction pattern of the silicon-oxygen composite material further includes diffraction peaks of silicon crystals, and the silicon-oxygen composite material satisfies at least one of the following relationships (1)-(2):
[0014] (1) 0.35≤Y / 2X≤4, optionally, 0.7≤Y / 2X≤4;
[0015] (2) -5≤5Xsin2θ-Y≤15, optionally, -5≤5Xsin2θ-Y≤10;
[0016] Wherein, Y is the grain size of the first doping element, X is the grain size of the silicon grains, the units of X and Y are both nm, and 2θ is the XRD diffraction angle of the crystal.
[0017] By controlling the grain size Y nm of the first doping element and the grain size X nm of the silicon grains to satisfy the following relationship: 0.35≤Y / 2X≤4 or -5≤5Xsin2θ-Y≤15, the battery has excellent cycle performance and rate performance, and the battery has a long cycle life.
[0018] In any embodiment, the XRD diffraction pattern of the silicon-oxygen composite material contains a diffraction peak of the first doping element crystal, the half-peak width of the diffraction peak of the crystal is 3°-7°, and / or the diffraction peak intensity of the crystal is 600S -1 -1200S -1 .
[0019] In any embodiment, based on the total mass of the silicon-oxygen composite material, the mass fraction of the first doping element is less than or equal to 12%, and can be optionally 1%-10%.
[0020] By controlling the mass content of the first doping element within a suitable range, the battery has excellent cycle performance and rate performance, and the battery has a long cycle life.
[0021] In any embodiment, the silicon-oxygen composite material further includes a second doping element, wherein the second doping element includes at least one of a non-metallic element, an alkali metal element, and an alkaline earth metal element, and the non-metallic element includes at least one of B, N, F, Cl, and S;
[0022] Optionally, the non-metallic element includes at least one of B, N, F, Cl, and S;
[0023] Optionally, the alkali metal element includes at least one of Li, Na, and K;
[0024] Optionally, the alkaline earth metal element includes at least one of Mg, Ca, Be, and Sr;
[0025] The silicon-oxygen composite material contains a second doping element, which can improve the discharge capacity retention rate of the battery at low temperatures and / or improve the energy density of the battery.
[0026] In any embodiment, based on the total mass of the silicon-oxygen composite material, the mass fraction of the second doping element is less than or equal to 7%, and can be optionally 1%-5%.
[0027] By controlling the mass fraction of the second doping element within a suitable range, the battery has excellent cycle performance and rate performance, and the battery has a long cycle life.
[0028] In any embodiment, the silicon-oxygen composite material further includes a carbon layer at least partially covering the surface of the silicon-oxygen material matrix. Optionally, the carbon layer has a thickness of 1-4 nm.
[0029] At least a portion of the surface of the silicon-oxygen composite material is covered with a carbon layer, so that the battery has excellent cycle performance and rate performance, and the battery has a long cycle life.
[0030] In any embodiment, the volume distribution particle size Dv50 of the silicon-oxygen composite material is 3-8 μm, and optionally 4-6 μm.
[0031] When the volume distribution particle size Dv50 of the silicon-oxygen composite material is within a suitable range, the battery has excellent cycle performance and rate performance, and the battery has a long cycle life.
[0032] In a second aspect of the present application, a method for preparing a silicon-oxygen composite material is provided, the preparation method comprising:
[0033] Performing a first vapor deposition on a first vapor containing silicon and silicon dioxide to obtain a silicon-oxygen material matrix;
[0034] A second vapor containing a first doping element is subjected to a second vapor deposition on a silicon oxide material matrix to obtain a silicon oxide composite material, wherein at least a portion of the first doping element exists in the silicon oxide material matrix in the form of crystals, and the grain size of the first doping element crystals is ≤9 nm, wherein the first doping element satisfies: the lithium ion diffusion coefficient of the first doping element at 25° C. is greater than the lithium ion diffusion coefficient of silicon at 25° C.
[0035] A bulk-doped silicon-oxygen composite material is obtained by vapor deposition. Bulk doping causes the first doping element to be uniformly dispersed and distributed within the silicon-oxygen material matrix at the atomic scale. The first doping element is distributed within the silicon-oxygen material matrix in the form of crystals, and the grain size of the crystals is less than or equal to 9 nm. This indicates that the first doping element is uniformly dispersed and distributed within the silicon-oxygen material matrix at the atomic scale, which can effectively reduce the migration energy barrier of lithium ions, increase the lithium ion diffusion coefficient, improve the lithium ion migration kinetics, extend the discharge time of the battery, and improve the battery's rate performance. In addition, the crystals formed by the first doping element are dispersed around the silicon grains, which can alleviate the growth of silicon clusters, effectively inhibit the expansion and pulverization effect of the silicon-oxygen composite material, enhance the structural integrity and volume stability of the silicon-oxygen composite material during the lithium insertion / extraction process, and improve the battery's cycle performance. In addition, the first doping element exists in the form of crystals with small grain size, which does not cause significant changes in the crystal structure of the silicon-oxygen material matrix or the phase properties of the material. It can well maintain the structural stability of the material and is not prone to pulverization during the charge and discharge process, thereby improving the battery's cycle performance and extending the battery's cycle life.
[0036] In any embodiment, the temperature of the first vapor deposition is 1000° C.-1300° C., optionally 1100° C.-1250° C.; and / or the time of the first vapor deposition is 6 h-12 h, optionally 8 h-10 h.
[0037] By controlling the temperature and / or time of the first vapor deposition within a suitable range, a silicon-oxygen material matrix with excellent performance and structural parameters can be obtained, which is beneficial to the subsequent element doping process.
[0038] In any embodiment, the temperature of the second vapor deposition is 800° C.-900° C., optionally 820° C.-880° C.; and / or the time of the second vapor deposition is 4 h-10 h, optionally 6 h-8 h.
[0039] By controlling the temperature and / or time of the second vapor deposition within an appropriate range, while achieving the bulk doping distribution of the first doping element, it is also possible to ensure that the first doping element exists in the silicon oxide material matrix in the form of small-sized crystals, thereby improving the conductivity of the material and improving the rate performance and cycle performance of the battery.
[0040] In any embodiment, the method for preparing the silicon-oxygen composite material comprises:
[0041] performing a second vapor deposition on the silicon-oxygen material matrix and a second vapor containing the first doping element and the second doping element to obtain the silicon-oxygen composite material, wherein the second doping element includes at least one of a non-metallic element, an alkali metal element, and an alkaline earth metal element;
[0042] Optionally, the non-metallic element includes at least one of B, N, F, Cl, and S;
[0043] Optionally, the alkali metal element includes at least one of Li, Na, and K;
[0044] Optionally, the alkaline earth metal element includes at least one of Mg, Ca, Be, and Sr.
[0045] Doping the second doping element in the form of vapor can achieve uniform bulk doping of the second doping element, thereby improving the discharge capacity retention rate of the battery at low temperatures and / or increasing the energy density of the battery.
[0046] In any embodiment, the preparation method further comprises:
[0047] Carrying out carbon coating treatment on the surface of the silicon-oxygen composite material;
[0048] Optionally, the temperature of the carbon coating treatment is 500°C-750°C, optionally 660°C-720°C;
[0049] Optionally, the carbon coating treatment time is 2h-10h, optionally 6h-8h.
[0050] Appropriate carbon coating treatment temperature and / or time, on the one hand, forms a uniformly distributed carbon layer structure of appropriate thickness on the surface of the silicon-oxygen composite material, which can buffer the volume change of the silicon-oxygen composite material during the lithium insertion and extraction process, while improving the electronic conductivity of the material surface, improving the cycle performance and rate performance of the battery. On the other hand, it can effectively control the grain size of the first doping element and the silicon grain size within a suitable range, so that the silicon-oxygen material has excellent structural parameters, thereby extending the discharge time of the battery, improving the rate performance of the battery, improving the cycle performance of the battery, and extending the cycle life of the battery.
[0051] A third aspect of the present application provides a secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises the silicon-oxygen composite material according to the first aspect or the silicon-oxygen composite material prepared by the preparation method of the second aspect.
[0052] A fourth aspect of the present application provides an electrical device comprising the secondary battery of the third aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] FIG1 is an XRD diagram of the silicon-oxygen composite material of Example 1 of the present invention;
[0054] FIG2 is a scanning electron microscope image of the silicon-oxygen composite material of Example 1 of the present invention;
[0055] FIG3 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0056] FIG4 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG3 ;
[0057] FIG5 is a schematic diagram of a battery module according to an embodiment of the present application;
[0058] FIG6 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0059] FIG7 is an exploded view of the battery pack according to one embodiment of the present application shown in FIG6 ;
[0060] FIG8 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.
[0061] Explanation of reference numerals: 1 battery pack; 2 upper case; 3 lower case; 4 battery module; 5 secondary battery; 51 housing; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION
[0062] Below, the embodiments of the binder, preparation method, electrode, battery, and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0063] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed in this application, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0064] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0065] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0066] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0067] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0068] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0069] In terms of new secondary battery negative electrode active materials, silicon-based negative electrode materials have attracted widespread attention due to their ultra-high lithium storage capacity and low voltage platform, making them ideal next-generation secondary negative electrode active materials. However, silicon-based materials have many problems during the process of charging, discharging, and deintercalating lithium ions: 1. The volume of silicon-based materials expands to 300% of its original volume during lithium ion insertion, and then shrinks sharply when lithium ions are released, causing the active material particles to break and the electrode sheets to fall off and pulverize, resulting in a sharp decrease in cycle life; 2. The irreversible capacity is large, and the initial coulombic efficiency of silicon-based materials is low. In particular, silicon oxide materials contain inactive components that can consume lithium ions, which produce a large amount of irreversible capacity during the initial charge and discharge process, making positive electrode matching difficult, low overall battery efficiency, and short cycle life; 3. In addition, silicon itself is a semiconductor with poor conductivity, which is not conducive to the rapid transfer of electrons, thus affecting the rate performance of silicon oxide materials.
[0070] [Silicon-oxygen composite materials]
[0071] Based on this, the present application proposes a silicon-oxygen composite material, which comprises a silicon-oxygen material matrix and a first doping element distributed in the silicon-oxygen material matrix, at least part of the first doping element exists in the silicon-oxygen material matrix in a crystalline form, and the grain size of the first doping element is ≤9nm, wherein the first doping element satisfies: the lithium ion diffusion coefficient of the first doping element at 25°C is greater than the lithium ion diffusion coefficient of silicon at 25°C.
[0072] The first doping element is distributed in the form of crystals inside the silicon oxide material matrix, and the grain size of the crystals is less than or equal to 9 nm, indicating that the first doping element is uniformly dispersed in the silicon oxide material matrix at the atomic scale, which can effectively reduce the migration energy barrier of lithium ions, increase the lithium ion diffusion coefficient, improve the lithium ion migration kinetics, improve the conductivity of the material, extend the discharge time of the battery, and improve the battery rate performance. In addition, the crystals formed by the first doping element are dispersed around the silicon grains, which can alleviate the growth of silicon clusters, effectively inhibit the expansion and pulverization effect of the silicon oxide composite material, enhance the structural integrity and volume stability of the silicon oxide composite material during the lithium insertion / extraction process, and improve the cycle performance of the battery. In addition, the first doping element exists in the form of crystals with small grain size, which will not cause major changes in the crystal structure of the silicon oxide material matrix, will not cause major changes in the phase properties of the material, can well maintain the structural stability of the material, is not easy to pulverize during the charge and discharge process, improves the cycle performance of the battery, and extends the cycle life of the battery.
[0073] Compared with the first doping element in an amorphous form, the first doping element in a crystalline form has better electrical conductivity and ion conductivity, can effectively increase the lithium ion diffusion coefficient, and improve the rate performance of the battery.
[0074] In summary, the silicon-oxygen composite material of the present application can be used as a negative electrode active material to extend the discharge time of the battery, improve the rate performance of the battery, extend the cycle life of the battery, and improve the cycle performance of the battery.
[0075] In this application, the grain size of the first doping element has a meaning well known in the art and can be measured using instruments and methods well known in the art. As an example, the XRD pattern of the silicon-oxygen composite material can be tested according to the JIS / K0131-1996 test standard. According to the XRD pattern of the silicon-oxygen composite material, the half-peak width β and the diffraction angle θ of the (101) crystal plane diffraction peak of the first doping element are taken and substituted into the Debye-Scherrer formula to calculate the crystal grain size. The Debye-Scherrer formula is as follows: Dhkl = kλ / (βcosθ), where Dhkl represents the crystal grain size, in nm; k represents the Scherrer constant, 0.89; λ represents the wavelength of the incident X-ray, 0.15406 nm; β represents the half-peak width of the diffraction peak, in rad; θ represents the diffraction angle, in degrees.
[0076] In some embodiments, the grain size of the first doping element may be selected to be less than or equal to 4 nm, less than or equal to 5 nm, less than or equal to 6 nm, less than or equal to 7 nm, less than or equal to 8 nm, or less than or equal to 9 nm.
[0077] In some embodiments, the first doping element includes at least two or more elements, and the grain size of the first doping element is an average value of grain sizes of the multiple first doping elements.
[0078] In this application, "lithium ion diffusion coefficient" refers to an important parameter used to characterize the kinetic behavior of a material. The larger the diffusion coefficient of a material, the better the high-current discharge capability of the battery, the higher the power density of the material, and the better the high-rate performance.
[0079] The type of “first doping element” in the present application refers to an element whose lithium ion diffusion coefficient of a single substance formed by the element is greater than the lithium ion diffusion coefficient of a single substance of silicon.
[0080] The lithium ion diffusion coefficient of a material has a well-known meaning in the art and can be measured using methods known in the art. As an example, this application uses a constant current intermittent titration (GITT) method to measure the lithium ion diffusion coefficient of a single material composed of a doping element.
[0081] In this application, the term "crystal" refers to a substance formed by a regular periodic arrangement of particles (molecules, atoms, ions) in three-dimensional space.
[0082] In some embodiments, the lithium ion diffusion coefficient of the first doping element at 25° C. is greater than 10 -14 cm 2 / S, can be greater than 10 -14 cm 2 / S and less than or equal to 10 -13 cm2 / S, the lithium ion diffusion coefficient of silicon at 25°C is less than 10 -14 cm 2 / S, can be greater than 10 - 15 cm 2 / S and less than 10 -14 cm 2 / S.
[0083] In some embodiments, the lithium ion diffusion coefficient of the first doping element at 25° C. can be 2×10 -14 cm 2 / S, 3×10 -14 cm 2 / S, 4×10 -14 cm 2 / S, 5×10 - 14 cm 2 / S, 6×10 -14 cm 2 / S、7×10 -14 cm 2 / S、8×10 -14 cm 2 / S, 9×10 -
[0084] 14 cm 2 / S, 10 -13 cm 2 Any value in / S or a range of any two values in it.
[0085] In some embodiments, the lithium ion diffusion coefficient of silicon at 25°C is greater than 10 -15 cm 2 / S and less than 10 -14 cm 2 / S. In some embodiments, the lithium ion diffusion coefficient of silicon at 25°C can be selected to be 2×10 -15 cm 2 / S, 3×10 -15 cm 2 / S, 4×10 - 15 cm 2 / S, 5×10 -15 cm 2 / S, 6×10 -15 cm 2 / S、7×10 -15 cm 2 / S、8×10 -
[0086] 15 cm 2 / S, 9×10 -15 cm 2 Any value in / S or a range of any two values in it.
[0087] In some embodiments, the first doping element includes at least one of Sn, Ge, Sb, Bi, and Sr.
[0088] In some embodiments, the first doping element includes at least two of Sn, Ge, Sb, Bi, and Sr. For example, the first doping element may include Ge and Sb, or the doping element may include Sn and Bi.
[0089] The first doping element has an excellent lithium ion diffusion coefficient, effectively improving the conductivity of the silicon-oxygen matrix and enhancing the battery's rate performance. Furthermore, the raw materials are abundant and readily available, making it suitable for use in a variety of batteries and offering excellent application prospects.
[0090] In some embodiments, the first doping element includes Sn.
[0091] Batteries in the prior art experience greater polarization at low SOC, especially more severe concentration polarization, which limits the battery's further application. The Sn doped in the silicon-oxygen composite material of this application has an excellent lithium ion diffusion coefficient, which can improve the conductivity of the electrode, reduce the degree of electrode polarization, enhance the battery's rate performance, and extend the battery's discharge time at low SOC, meeting new usage scenarios.
[0092] In the application, the term "battery polarization" refers to the phenomenon that an electrode deviates from the equilibrium electrode potential when current passes through the electrode. The equilibrium electrode potential is the electrode potential when no current passes through the battery, including ohmic polarization, electrochemical polarization and concentration polarization.
[0093] In the application, the term "concentration polarization" refers to the polarization caused by the diffusion rate of lithium ions participating in the reaction in the solid phase being slower than the electrochemical reaction rate.
[0094] In some embodiments, the grain size of the first doping element is ≤7 nm.
[0095] In some embodiments, a grain size of the first doping element is less than or equal to 4 nm, less than or equal to 5 nm, less than or equal to 6 nm, or less than or equal to 7 nm.
[0096] Controlling the grain size of the first doping element within a suitable range can further extend the discharge time of the battery, further improve the rate performance and cycle performance of the battery, and extend the cycle life of the battery.
[0097] In some embodiments, the XRD diffraction pattern of the silicon-oxygen composite material further includes diffraction peaks of silicon crystals, and the silicon-oxygen composite material satisfies at least one of the following relationships (1)-(2):
[0098] (1) 0.35≤Y / 2X≤4, optionally, 0.7≤Y / 2X≤4;
[0099] (2) -5≤5Xsin2θ-Y≤15, optionally, -5≤5Xsin2θ-Y≤10;
[0100] Wherein, Y is the grain size of the first doping element, X is the grain size of the silicon grains, the units of X and Y are both nm, and 2θ is the XRD diffraction angle of the crystal.
[0101] In some embodiments, the silicon-oxygen composite material satisfies the following relationship: 0.35≤Y / 2X≤4, where Y is the grain size of the first doping element, and X is the grain size of the silicon grains.
[0102] In some embodiments, the silicon-oxygen composite material has any one of the following relationships: 0.35≤Y / 2X≤1, 0.35≤Y / 2X≤0.7, 0.35≤Y / 2X≤1, 0.35≤Y / 2X≤2, 0.35≤Y / 2X≤3, 0.35≤Y / 2X≤4, 0.7≤Y / 2X≤1, 0.7≤Y / 2X≤2, 0.7≤Y / 2X≤3, 0.35≤Y / 2X≤4, 1≤Y / 2X≤2, 1≤Y / 2X≤3, 1≤Y / 2X≤4, 2≤Y / 2X≤3, 2≤Y / 2X≤3, 2≤Y / 2X≤4, and 3≤Y / 2X≤4.
[0103] In this article, the grain size of silicon grains has a meaning well known in the art and can be tested using methods known in the art. As an example, the XRD pattern of the silicon-oxygen composite material can be tested according to the JIS / K0131-1996 test standard. According to the XRD pattern of the silicon-oxygen composite material, the half-peak width β and the diffraction angle θ of the Si (111) crystal plane diffraction peak are taken and substituted into the Debye-Scherrer formula to calculate the grain size of the silicon grains. The Debye-Scherrer formula is as follows: Dhkl = kλ / (βcosθ), where Dhkl represents the grain size of the silicon grains, in nm; k represents the Scherrer constant, 0.89; λ represents the wavelength of the incident X-ray, 0.15406 nm; β represents the half-peak width of the diffraction peak, in rad; θ represents the diffraction angle, in degrees.
[0104] Silicon grains with an appropriate grain size can reduce the volume expansion of the silicon-oxygen material matrix during charge and discharge, reducing the pulverization of the material. Furthermore, appropriately sized silicon grains can effectively shorten the distance lithium ions travel during charge and discharge, which helps improve the rate performance of silicon-oxygen composite materials.
[0105] Crystals formed by the first doping element are dispersed around the silicon grains, mitigating the growth of silicon clusters. Both the crystal grain size and the silicon grain size affect the size of the silicon clusters, and the formation of large silicon clusters deteriorates the rate and cycle performance of the battery. Therefore, the crystal grain size Y nm and the silicon grain size X nm are controlled within the range of 0.35 ≤ Y / 2X ≤ 4. This coordinated coordination of the crystal grain size and silicon grain size effectively reduces the likelihood of large silicon clusters, resulting in excellent cycle and rate performance and a long cycle life for the battery.
[0106] In some embodiments, the silicon-oxygen composite material satisfies the following relationship: 0.7≤Y / 2X≤4, where Y nm is the grain size of the crystal, and X nm is the grain size of the silicon grains in the silicon-oxygen composite material.
[0107] In some embodiments, the silicon-oxygen composite material has any one of the following relationships: 0.7≤Y / 2X≤1, 0.7≤Y / 2X≤0.7, 0.7≤Y / 2X≤1, 0.7≤Y / 2X≤2, 0.7≤Y / 2X≤3, 0.7≤Y / 2X≤4, 1≤Y / 2X≤2, 1≤Y / 2X≤3, 1≤Y / 2X≤4, 2≤Y / 2X≤3, 2≤Y / 2X≤3, 2≤Y / 2X≤4, 3≤Y / 2X≤4.
[0108] By controlling the crystal grain size Y nm and the silicon grain size X nm within the numerical range of 0.7≤Y / 2X≤4, and by the coordinated coordination of the crystal grain size and the silicon grain size, the possibility of generating large-grain silicon clusters can be effectively reduced, thereby further improving the cycle performance of the battery.
[0109] In some embodiments, the XRD diffraction pattern of the silicon-oxygen composite material further includes diffraction peaks of silicon crystals, and the silicon-oxygen composite material has the following relationship: -5≤5Xsin2θ-Y≤15,
[0110] Wherein, Y is the grain size of the first doping element, X is the grain size of the silicon grains, the units of X and Y are both nm, and 2θ is the XRD diffraction angle of the crystal.
[0111] In some embodiments, the silicon-oxygen composite material has any one of the following relationships:
[0112] -5≤5Xsin2θ-Y≤0、-5≤5Xsin2θ-Y≤5、-5≤5Xsin2θ-Y≤10、
[0113] -5≤5Xsin2θ-Y≤15、0≤5Xsin2θ-Y≤5、0≤5Xsin2θ-Y≤10、
[0114] 0≤5Xsin2θ-Y≤15、5≤5Xsin2θ-Y≤10、5≤5Xsin2θ-Y≤15、
[0115] 10≤5Xsin2θ-Y≤15.
[0116] In some embodiments, the first doping element includes two or three elements, and 2θ is an average value of the two or three doping elements.
[0117] The crystals formed by the first doping element are dispersed around the silicon grains, mitigating the growth of silicon clusters. Both the crystal grain size and the silicon grain size affect the size of the silicon clusters, and the formation of large silicon clusters deteriorates the battery's rate and cycle performance. Furthermore, different first doping elements have varying degrees of influence on the material's rate and cycle performance. Therefore, controlling the crystal grain size (Y nm), silicon grain size, and XRD diffraction angle within the range of -5 ≤ 5Xsin2θ - Y ≤ 15 results in excellent battery cycle and rate performance, and a long cycle life.
[0118] In some embodiments, the XRD diffraction pattern of the silicon-oxygen composite material further includes diffraction peaks of silicon crystals, and the silicon-oxygen composite material has the following relationship: -5≤5Xsin2θ-Y≤10,
[0119] Wherein, Y is the grain size of the first doping element, X is the grain size of the silicon grains, the units of X and Y are both nm, and 2θ is the XRD diffraction angle of the crystal.
[0120] In some embodiments, the silicon-oxygen composite material has any one of the following relationships:
[0121] -5≤5Xsin2θ-Y≤0、-5≤5Xsin2θ-Y≤5、-5≤5Xsin2θ-Y≤10、
[0122] 0≤5Xsin2θ-Y≤5, 0≤5Xsin2θ-Y≤10, 5≤5Xsin2θ-Y≤10.
[0123] By controlling the crystal grain size Y nm, the grain size of the silicon grains and the XRD diffraction angle of the crystal within the numerical range of -5≤5Xsin2θ-Y≤10, the cycle life of the battery can be further improved.
[0124] In some embodiments, the XRD diffraction pattern of the silicon-oxygen composite material includes a crystal diffraction peak, and the half-maximum width of the crystal diffraction peak is 3°-7°.
[0125] In some embodiments, the diffraction peak intensity of the crystal is 600S -1 -1200S -1 .
[0126] In some embodiments, the half-value width of the diffraction peak of the crystal is any value of 3°, 4°, 5°, 6°, 7°, or a range consisting of any two values thereof.
[0127] In some embodiments, the diffraction peak intensity of the crystal is 600S -1 , 700S -1 、800S - 1 、900S -1 、1000S -1 、1100S -1 、1200S -1 Any value in , or a range of any two values in .
[0128] In some embodiments, the first doping element includes two or more elements, and the diffraction peak intensity and diffraction peak half-maximum width of the crystal are the average values of the diffraction peak intensity and diffraction peak half-maximum width of the two or more first doping elements.
[0129] The diffraction peak half-width and diffraction peak intensity of a crystal are well known in the art and can be measured using methods known in the art. As an example, an XRD pattern of a silicon-oxygen composite material can be measured according to the JIS / K0131-1996 testing standard, and the diffraction peak half-width and diffraction peak intensity of the crystal can be obtained based on the XRD pattern of the silicon-oxygen composite material.
[0130] The half-maximum width of the diffraction peak of the crystal is within a suitable range, the crystal has a suitable grain size, the battery has excellent cycle performance and rate performance, and the battery has a long cycle life.
[0131] The diffraction peak intensity of the crystal is within an appropriate range, indicating that the crystal has a high degree of crystallinity, which can effectively reduce the migration energy barrier of lithium ions, increase the lithium ion diffusion coefficient, and improve the lithium ion migration kinetics. The battery has excellent cycle performance and rate performance, and the battery has a long cycle life.
[0132] In some embodiments, the mass fraction of the first doping element is less than or equal to 12% based on the total mass of the silicon-oxygen composite material. In some embodiments, the mass fraction of the first doping element can be any one of less than or equal to 1%, less than or equal to 2%, less than or equal to 3%, less than or equal to 4%, less than or equal to 5%, less than or equal to 6%, less than or equal to 7%, less than or equal to 8%, less than or equal to 9%, less than or equal to 10%, less than or equal to 11%, or less than or equal to 12% based on the total mass of the silicon-oxygen composite material.
[0133] The mass content of the first doping element in the silicon-oxygen composite material can be tested using methods and equipment known in the art, for example, it can be measured with reference to EPA 6010D-2014 standard; specifically, ICP-OES (elemental analysis-inductively coupled plasma optical emission spectrometry) testing can be used, wherein the sample to be tested is first dissolved into a liquid with a strong acid, and then the liquid is introduced into an ICP light source by atomization. The gaseous atoms to be tested are further ionized and excited in a strong magnetic field, and then restored to the ground state from the excited state; in the above process, energy is released and recorded as different characteristic spectral lines for elemental quantitative analysis.
[0134] The first doping element has an appropriate mass content, which can improve the electrical conductivity of the silicon-oxygen composite material, improve the lithium ion transmission capacity of the material, and improve the cycle performance and rate performance of the battery. At the same time, the first doping element with an appropriate mass content will not change the internal structure and crystal phase of the material, thereby improving the cycle performance of the battery.
[0135] In some embodiments, the mass fraction of the first doping element is 1%-10% based on the total mass of the silicon-oxygen composite material. In some embodiments, the mass fraction of the first doping element is 1%-9%, 1%-8%, 1%-7%, 1%-6%, 1%-5%, 1%-4%, 1%-3%, 2%-10%, 2%-9%, 2%-8%, 2%-7%, 2%-6%, 2%-5%, 2%-4%, 3%-10%, 3%-9%, 3%-8%, 3%-7%, 3%-6%, 3%-5%, 4%-10%, 4%-9%, 4%-8%, 4%-7%, etc. based on the total mass of the silicon-oxygen composite material.
[0136] By controlling the mass content of the first doping element within a suitable range, the conductivity of the silicon-oxygen composite material can be further improved, the discharge time of the battery can be extended, and the rate performance of the battery can be improved.
[0137] In some embodiments, the silicon-oxygen composite material further includes a second doping element, and the second doping element includes at least one of a non-metallic element, an alkali metal element, and an alkaline earth metal element.
[0138] In some embodiments, the non-metallic element includes at least one of B, N, F, Cl, and S.
[0139] In some embodiments, the alkali metal element includes at least one of Li, Na, and K.
[0140] In some embodiments, the alkaline earth metal element includes at least one of Mg, Ca, Be, and Sr.
[0141] In some embodiments, the second doping element includes a non-metallic element.
[0142] At low temperatures, the diffusion ability of active ions in silicon-oxygen composite materials decreases, and the charge transfer impedance increases significantly. By adding non-metallic elements, the charge transfer impedance can be reduced, the discharge capacity retention rate of the battery at low temperatures can be improved, and the battery's performance at low temperatures can be improved.
[0143] In some embodiments, the second doping element includes at least one of an alkali metal and an alkaline earth metal.
[0144] Alkali metals and alkaline earth metals are active towards lithium and can increase the specific capacity of silicon-oxygen composite materials and improve the energy density of batteries.
[0145] In some embodiments, the mass fraction of the second doping element is less than or equal to 7% based on the total mass of the silicon-oxygen composite material. In some embodiments, the mass fraction of the second doping element is less than or equal to 1%, less than or equal to 2%, less than or equal to 3%, less than or equal to 4%, less than or equal to 5%, less than or equal to 6%, or less than or equal to 7% based on the total mass of the silicon-oxygen composite material.
[0146] The mass content of the second doping element in the silicon-oxygen composite material can be tested using methods and equipment known in the art, for example, it can be measured with reference to EPA 6010D-2014 standard; specifically, ICP-OES (elemental analysis-inductively coupled plasma optical emission spectrometry) testing can be used, wherein the sample to be tested is first dissolved into a liquid with a strong acid, and then the liquid is introduced into an ICP light source by atomization. The gaseous atoms to be tested are further ionized and excited in a strong magnetic field, and then restored to the ground state from the excited state; in the above process, energy is released and recorded as different characteristic spectral lines for elemental quantitative analysis.
[0147] By controlling the mass fraction of the second doping element within a suitable range, the battery has excellent cycle performance and rate performance, and the battery has a long cycle life.
[0148] In some embodiments, the mass fraction of the second doping element is 1%-5% based on the total mass of the silicon-oxygen composite material. In some embodiments, the mass fraction of the second doping element is any one of 1%-2%, 1%-3%, 1%-4%, 1%-5%, 2%-3%, 2%-4%, 2%-5%, 3%-4%, 3%-5%, and 4%-5% based on the total mass of the silicon-oxygen composite material.
[0149] Controlling the mass fraction of the second doping element within an appropriate range can further extend the discharge time of the battery, improve the cycle performance and rate performance of the battery, and extend the cycle life of the battery.
[0150] In some embodiments, the silicon-oxygen composite material further includes a carbon layer at least partially covering the surface of the silicon-oxygen material matrix.
[0151] The carbon layer formed on the surface of the silicon-oxygen material matrix can effectively inhibit the particle breakage and pulverization of the silicon-oxygen composite material during the charge and discharge cycle, alleviate the volume expansion of the silicon-oxygen composite material, and ensure the structural stability of the silicon-oxygen composite material. After being coated with the carbon layer, the silicon-oxygen composite material has better conductivity and stability, which can improve the cycle stability and rate performance of the battery.
[0152] In some embodiments, the carbon layer has a thickness of 1-4 nm.
[0153] The thickness of the carbon layer has a well-known meaning in the art and can be tested using methods known in the art. As an example, the silicon-oxygen composite material is embedded and cured with epoxy resin, and then the ultrathin sectioning method is used to cut out complete particles to prepare a sample. A cross-section of the particle sample is selected for observation using a high-power transmission electron microscope to observe the long-range regularly arranged and ordered regions, namely the silicon-oxygen material matrix. The amorphous region (no long-range regular lamellae, and the lamellae are arranged in a disorderly manner) coated on the surface of the silicon-oxygen material matrix is the carbon layer region. The average thickness of the carbon layer is obtained by multiple measurements.
[0154] In some embodiments, the volume distribution particle size Dv50 of the silicon-oxygen composite material is 3-8 μm.
[0155] In some embodiments, the volume distribution particle size Dv50 of the silicon-oxygen composite material can be selected as any one of 3-4 μm, 3-5 μm, 3-6 μm, 3-7 μm, 3-8 μm, 4-5 μm, 4-6 μm, 4-7 μm, 4-8 μm, 5-6 μm, 5-7 μm, 5-8 μm, 6-7 μm, 7-8 μm, and 6-8 μm.
[0156] The volume distribution particle size Dv50 of the silicon-oxygen composite material is well known in the art and can be measured using methods known in the art. As an example, the silicon-oxygen composite material sample is measured according to the GB / T19077-2016 / ISO 13320:2009 standard, and the testing equipment can be a laser particle size analyzer (such as the Malvern Master Size 3000).
[0157] By controlling the volume distribution particle size Dv50 of the silicon-oxygen composite material within an appropriate range, the structure of the silicon-oxygen composite material is relatively stable and the kinetic performance is relatively good, which is beneficial to improving the cycle performance and rate performance of the battery.
[0158] In some embodiments, the volume distribution particle size Dv50 of the silicon-oxygen composite material is 4-6 μm.
[0159] In some embodiments, the volume distribution particle size Dv50 of the silicon-oxygen composite material can be selected from any one of 4-6 μm, 4-7 μm, 4-8 μm, and 5-6 μm.
[0160] Controlling the volume distribution particle size Dv50 of the silicon-oxygen composite material within an appropriate range can further increase the lithium ion transmission speed, improve the conductivity of the material, further extend the discharge time of the battery, improve the battery's cycle performance and rate performance, and extend the battery's cycle life.
[0161] In some embodiments, a method for preparing a silicon-oxygen composite material is provided, the method comprising:
[0162] Performing a first vapor deposition on a first vapor containing silicon and silicon dioxide to obtain a silicon-oxygen material matrix;
[0163] A second vapor containing a first doping element is subjected to a second vapor deposition on a silicon oxide material matrix to obtain a silicon oxide composite material, wherein at least a portion of the first doping element exists in the silicon oxide material matrix in the form of crystals, and the grain size of the first doping element crystals is ≤9 nm, wherein the first doping element satisfies: the lithium ion diffusion coefficient of the first doping element at 25° C. is greater than the lithium ion diffusion coefficient of silicon at 25° C.
[0164] In this application, the term "vapor deposition" refers to a process in which a gaseous or vaporous substance reacts in a gas phase or at a gas-solid interface to form a solid deposit.
[0165] A bulk-doped silicon-oxygen composite material is obtained by vapor deposition. Bulk doping allows the first doping element to be uniformly dispersed within the silicon-oxygen matrix at the atomic scale. The first doping element is distributed within the silicon-oxygen matrix in the form of crystals with a grain size of 9 nm or less. This indicates that the first doping element is uniformly dispersed within the silicon-oxygen matrix at the atomic scale, effectively reducing the lithium ion migration energy barrier, increasing the lithium ion diffusion coefficient, and enhancing the lithium ion migration kinetics, thereby extending the battery's discharge time and improving the battery's rate performance. Furthermore, the crystals formed by the first doping element are dispersed around the silicon grains, which can mitigate the growth of silicon clusters and effectively inhibit the expansion and pulverization effect of the silicon-oxygen composite material. This enhances the structural integrity and volume stability of the silicon-oxygen composite material during lithium insertion and extraction, thereby improving the battery's cycling performance. Furthermore, the first doping element exists in the form of small crystals, which do not significantly alter the crystal structure of the silicon-oxygen matrix or the phase properties of the material. This maintains the material's structural stability and prevents pulverization during charge and discharge, thereby improving the battery's cycling performance and extending its cycle life.
[0166] In some embodiments, the temperature of the first vapor deposition is 1000°C-1300°C.
[0167] In some embodiments, the temperature of the first vapor deposition is 1100°C-1250°C.
[0168] In some embodiments, the temperature of the first vapor deposition is any value of 1000° C., 1100° C., 1200° C., 1250° C., 1300° C., or a range consisting of any two values thereof.
[0169] In some embodiments, the first vapor deposition time is 6 hours to 12 hours.
[0170] In some embodiments, the first vapor deposition time is 8 hours to 10 hours.
[0171] In some embodiments, the time for the first vapor deposition is any value among 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, or a range consisting of any two values therein.
[0172] By controlling the temperature and / or time of the first vapor deposition within a suitable range, a silicon-oxygen material matrix with excellent performance and structural parameters can be obtained, which is beneficial for the subsequent element doping process.
[0173] In some embodiments, the grain size of silicon dioxide is 1-4 nm. In some embodiments, the grain size of silicon dioxide can be selected from any one of 1-2 nm, 1-3 nm, 1-4 nm, 2-3 nm, 2-4 nm, and 3-4 nm.
[0174] By controlling the grain size of the raw silicon dioxide within a suitable range, the grain size of the silicon grains in the silicon-oxygen composite material is also within a suitable range, thereby avoiding the formation of silicon clusters with large grain sizes, effectively inhibiting the expansion and pulverization effect of the silicon-oxygen composite material, and improving the cycle stability of the battery.
[0175] In some embodiments, the temperature of the second vapor deposition is 800°C-900°C.
[0176] In some embodiments, the temperature of the second vapor deposition is 820°C-880°C.
[0177] In some embodiments, the temperature of the second vapor deposition is any value of 800° C., 820° C., 880° C., 900° C., or a range consisting of any two of these values.
[0178] In some embodiments, the second vapor deposition time is 4 hours to 10 hours.
[0179] In some embodiments, the second vapor deposition time is 6 hours to 8 hours.
[0180] In some embodiments, the time for the second vapor deposition is any value among 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, or a range consisting of any two values therein.
[0181] By controlling the temperature and / or time of the second vapor deposition within an appropriate range, the bulk doping distribution of the first doping element is achieved while ensuring that the first doping element exists in the silicon oxide material matrix in the form of crystals with small grain size, thereby improving the conductivity of the material, avoiding the formation of large crystals, and improving the rate performance and cycle performance of the battery.
[0182] In some embodiments, the method for preparing the silicon-oxygen composite material comprises:
[0183] A second vapor containing a first doping element and a second doping element is subjected to a second vapor deposition on the silicon-oxygen material matrix to obtain a silicon-oxygen composite material, wherein the second doping element includes at least one of a non-metallic element, an alkali metal element, and an alkaline earth metal element;
[0184] In some embodiments, the non-metallic element includes at least one of B, N, F, Cl, and S;
[0185] In some embodiments, the alkali metal element includes at least one of Li, Na, and K;
[0186] In some embodiments, the alkaline earth metal element includes at least one of Mg, Ca, Be, and Sr.
[0187] Doping the second doping element in the form of vapor can achieve uniform bulk doping of the second doping element, thereby improving the discharge capacity retention rate of the battery at low temperatures and / or improving the energy density of the battery.
[0188] In some embodiments, the preparation method further comprises:
[0189] The surface of the silicon-oxygen composite material is subjected to carbon coating treatment.
[0190] In some embodiments, the temperature of the carbon coating treatment is 500°C-750°C.
[0191] In some embodiments, the temperature of the carbon coating treatment is 660°C-720°C.
[0192] In some embodiments, the temperature of the carbon coating treatment is any value of 500° C., 550° C., 600° C., 660° C., 720° C., 750° C., or a range consisting of any two of these values.
[0193] In some embodiments, the carbon coating treatment time is 2 hours to 10 hours.
[0194] In some embodiments, the carbon coating treatment time is 6 hours to 8 hours.
[0195] In some embodiments, the carbon coating treatment time is any value among 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, or a range consisting of any two values therein.
[0196] Appropriate carbon coating treatment temperature and / or time, on the one hand, forms a uniformly distributed carbon layer structure of appropriate thickness on the surface of the silicon-oxygen composite material, which can buffer the volume change of the silicon-oxygen composite material during the lithium insertion and extraction process, while improving the electronic conductivity of the material surface, improving the cycle performance and rate performance of the battery. On the other hand, it can effectively control the grain size of the first doping element and the silicon grain size within a suitable range, so that the silicon-oxygen material has excellent structural parameters, thereby extending the discharge time of the battery, improving the rate performance of the battery, improving the cycle performance of the battery, and extending the cycle life of the battery.
[0197] [Negative electrode]
[0198] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0199] In some embodiments, a negative electrode plate is provided, comprising a negative electrode active material. The negative electrode active material comprises the silicon-oxygen composite material in some embodiments or the silicon-oxygen composite material prepared by the preparation method in some embodiments.
[0200] The electrode has excellent conductivity and cycle stability and has a high specific capacity.
[0201] In some embodiments, the mass content of the silicon-oxygen composite material is greater than or equal to 20% based on the total mass of the negative electrode active material. In some embodiments, the mass content of the silicon-oxygen composite material is selected from any one of greater than or equal to 20%, greater than or equal to 30%, greater than or equal to 40%, greater than or equal to 50%, greater than or equal to 60%, greater than or equal to 70%, greater than or equal to 80%, and greater than or equal to 90% based on the total mass of the negative electrode active material.
[0202] The mass content of the silicon-oxygen composite material is within an appropriate range, so that the silicon-oxygen composite material has a high theoretical specific capacity. In addition, the silicon-oxygen composite material with an appropriate content has good conductivity and the battery has excellent rate performance.
[0203] In some embodiments, the mass content of the silicon-oxygen composite material is 25%-90% based on the total mass of the negative electrode active material. In some embodiments, the mass content of the silicon-oxygen composite material can be 25%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, or a value in a range consisting of any two of the above values, based on the total mass of the negative electrode active material.
[0204] By controlling the silicon-oxygen composite material within an appropriate range, the energy density and cycle life of the battery can be taken into account, and the electrochemical performance of the battery can be comprehensively improved.
[0205] In some embodiments, the present application further provides a secondary battery, which includes the negative electrode sheet in any embodiment.
[0206] In some embodiments, the energy density of the secondary battery is 400-500 Wh / kg.
[0207] At 25°C, allow the secondary battery to rest for 2 hours. Charge the secondary battery at 0.1C to the charge cutoff voltage. Continue constant-voltage charging at the charge cutoff voltage until the current reaches 0.05C, at which point the charge is cut off (where C represents the rated capacity of the battery cell). Allow the secondary battery to rest at 25°C for 1 hour. Discharge the secondary battery at 0.1C to the discharge cutoff voltage. Record the total discharge capacity (C0) and the total discharge energy (E0).
[0208] Secondary battery mass measurement: Place the secondary battery on an electronic balance until the mass is stable, and read the mass value M0 of the secondary battery.
[0209] Secondary battery mass energy density = E0 / M0.
[0210] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0211] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0212] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0213] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0214] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0215] In some embodiments, the negative electrode film layer may optionally further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0216] In some embodiments, the negative electrode sheet of a full battery can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet of the full battery can be obtained.
[0217] [Positive electrode]
[0218] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.
[0219] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.
[0220] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0221] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.
[0222] In some embodiments, the positive electrode film layer may further include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0223] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0224] [Electrolytes]
[0225] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.
[0226] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.
[0227] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0228] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0229] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.
[0230] [Isolation film]
[0231] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.
[0232] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0233] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0234] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0235] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0236] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG3 shows a secondary battery 5 having a square structure as an example.
[0237] In some embodiments, referring to Figure 4, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0238] In some embodiments, secondary batteries can be assembled into a battery module. The number of secondary batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.
[0239] Figure 5 shows an example battery module 4. Referring to Figure 5 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.
[0240] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0241] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.
[0242] Figures 6 and 7 illustrate an example battery pack 1. Referring to Figures 6 and 7 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be positioned over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0243] In addition, the present application also provides an electric device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.
[0244] As the electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0245] Figure 8 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.
[0246] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.
[0247] The lithium ion diffusion coefficient data of the first doping element and silicon used in the following embodiments are as follows:
[0248] The lithium ion diffusion coefficient of Sn element at 25℃ is 1×10 -13 cm 2 / S;
[0249] The lithium ion diffusion coefficient of Ge element at 25℃ is 5×10 -14 cm 2 / S;
[0250] The lithium ion diffusion coefficient of Sb element at 25℃ is 7×10 -14 cm 2 / S;
[0251] The lithium ion diffusion coefficient of Bi element at 25℃ is 4×10 -13 cm 2 / S;
[0252] The lithium ion diffusion coefficient of Sr element at 25℃ is 6×10 -13 cm 2 / S;
[0253] The lithium ion diffusion coefficient of element B at 25°C is 10 -16 cm 2 / S;
[0254] The lithium ion diffusion coefficient of silicon at 25°C is 2×10 -15 cm 2 / S.
[0255] Example
[0256] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0257] Example 1
[0258] (1) Preparation of positive electrode sheet
[0259] LiNi 0.98 Co 0.01 Mn 0.01 O2, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are added to the solvent N-methylpyrrolidone in a mass ratio of 97%:1%:2%, and the mixture is mixed and stirred evenly to obtain the positive electrode slurry; then it is evenly coated on the positive electrode collector, and the positive electrode sheet is obtained after drying, cold pressing, and cutting.
[0260] (2) Preparation of negative electrode sheet
[0261] 1) Preparation of silicon-oxygen composite materials
[0262] 900g Si powder and 1200g SiO2 powder were mixed to obtain a silicon source, which was added to the heating chamber 1 of a vacuum furnace, and the vacuum was evacuated to below 1Pa and heating began. After heating to 1300°C, it entered the deposition system and was deposited at 1200°C for 6.6h to obtain a silicon oxide material matrix; 30g tin metal was added to the heating chamber 2, and then the vacuum was evacuated to below 10Pa and heating began. After heating to 1100°C, it entered the deposition system and was deposited at 830°C for 6.2h. After naturally cooling to room temperature, a block-shaped deposition material was obtained.
[0263] The obtained deposited material was crushed into particles with a median particle size of 5 μm by air flow milling, and added to a CVD vapor deposition furnace for carbon coating treatment. Acetylene gas was introduced at a mass flow rate of 700 sccm and deposited at 680°C for 5 hours. The coated material was placed under nitrogen protection and heated to 800°C at a heating rate of 5°C / min and kept at that temperature for 1 hour. After natural cooling, a silicon-oxygen composite material was obtained.
[0264] 2) Preparation of negative electrode sheet: artificial graphite and the silicon-oxygen composite material prepared above are mixed in a mass ratio of 3:7 to obtain a negative electrode active material, the negative electrode active material, conductive agent carbon black, carbon nanotubes (CNT), binder styrene-butadiene rubber (SBR), thickener sodium carboxymethyl cellulose (CMC) are added to deionized water in a weight ratio of 94.5%:1%:0.375%:2.8%:1.325%, and mixed and stirred to obtain a negative electrode slurry; the slurry is coated on the negative electrode current collector, and the negative electrode sheet is obtained after drying, cold pressing, and slitting.
[0265] (3) Isolation film
[0266] Polypropylene film is used as the isolation film.
[0267] (4) Preparation of electrolyte
[0268] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), the organic solvents ethylene carbonate, ethyl methyl carbonate, diethyl carbonate, and fluoroethylene carbonate (FEC) were mixed in a volume ratio of 1:1:1:1, and LiPF6 was added and dissolved in the organic solvent to make the concentration of the electrolyte 1 mol / L to obtain the electrolyte of Example 1.
[0269] (5) Preparation of secondary batteries
[0270] The positive electrode sheet, separator, and negative electrode sheet of Example 1 are stacked in order, with the separator placed between the positive and negative electrode sheets to serve as an isolation. The cells are then wound to obtain battery cells, the tabs are welded to the battery cells, and the battery cells are placed in an aluminum shell. The electrolyte is then injected and sealed. After standing, cold pressing, formation, shaping, capacity testing, and other processes, a lithium-ion secondary battery is obtained.
[0271] The preparation parameters in Examples 2-5 are basically the same as those in Example 1, except that the first doping metal element is different. The specific parameters are shown in Table 1. Specifically,
[0272] Example 2:
[0273] 900g of Si powder was mixed with 1200g of SiO2 powder with a grain size of 3nm to obtain a silicon source, which was added to the heating chamber 1 of a vacuum furnace, and the vacuum was evacuated to below 1Pa and heating began. After heating to 1300℃, it entered the deposition system and was deposited at 1160℃ for 6.7h to obtain a silicon oxide material matrix; 30g of germanium metal was added to the heating chamber 2, and then the vacuum was evacuated to below 12Pa and heating began. After heating to 1100℃, it entered the deposition system and was deposited at 828℃ for 6.4h. After naturally cooling to room temperature, a block-shaped deposition material was obtained.
[0274] Example 3:
[0275] 900g of Si powder was mixed with 1200g of SiO2 powder with a grain size of 2nm to obtain a silicon source, which was added to the heating chamber 1 of a vacuum furnace, and the vacuum was evacuated to below 1Pa and heating began. After heating, it entered the deposition system and was deposited at 1170°C for 6.5h to obtain a silicon oxide material matrix; 30g of antimony metal was added to the heating chamber 2, and then the vacuum was evacuated to below 10Pa and heating began. After heating to 1100°C, it entered the deposition system and was deposited at 827°C for 6.9h. After naturally cooling to room temperature, a block-shaped deposition material was obtained.
[0276] Embodiment 4:
[0277] 900g of Si powder was mixed with 1200g of SiO2 powder with a grain size of 2nm to obtain a silicon source, which was added to the heating chamber 1 of a vacuum furnace, and the vacuum was evacuated to below 1Pa and heating began. After heating, it entered the deposition system and was deposited at 1180°C for 6.4h to obtain a silicon oxide material matrix; 30g of bismuth metal was added to the heating chamber 2, and then the vacuum was evacuated to below 10Pa and heating began. After heating to 1250°C, it entered the deposition system and was deposited at 826°C for 6.8h. After naturally cooling to room temperature, a block-shaped deposition material was obtained.
[0278] Example 5:
[0279] 900g of Si powder was mixed with 1200g of SiO2 powder with a grain size of 2nm to create a silicon source. This was then placed in the first chamber of a vacuum furnace, where the vacuum was evacuated to below 1Pa and heating began. After heating to 1300°C, the material entered the deposition system and was deposited at 1190°C for 6.8 hours to obtain the silicon-oxygen material matrix. 15g of tin metal was added to the second chamber, where the vacuum was evacuated to below 10Pa and heating began to 1100°C. 15g of germanium metal was added to the third chamber, where the vacuum was evacuated to below 12Pa and heating began to 1100°C. The vapor in chambers 2 and 3 entered the deposition system, where deposition was carried out at 825°C for 6.7 hours. After cooling naturally to room temperature, the deposited material was formed into a bulk form.
[0280] Examples 6-11
[0281] The preparation parameters of Examples 6-11 are basically the same as those of Example 1, except that the temperature and time of the first vapor deposition, the temperature and time of the second vapor deposition, and the treatment temperature of the carbon coating are different. The specific parameters are shown in Table 1.
[0282] Examples 12-16
[0283] The preparation parameters of Examples 12-16 are basically the same as those of Example 1, except that the temperature and time of the first vapor deposition, the temperature and time of the second vapor deposition, and the treatment temperature of the carbon coating are different. In addition, the mass of tin metal is adjusted to 15g, 45g, 150g, 7.5g, and 180g, respectively, and the mass content of tin is adjusted. The specific parameters are shown in Table 1.
[0284] Examples 17-18
[0285] The preparation parameters of Examples 17-18 are basically the same as those of Example 1, except that a second doping element, boron or lithium, is further included. Specifically,
[0286] Example 17
[0287] 900g of Si powder was mixed with 1200g of SiO2 powder with a grain size of 2nm to create a silicon source. This was then placed in heating chamber 1 of a vacuum furnace, where the vacuum was evacuated to below 1Pa and heating began. After heating to 1300°C, the material entered the deposition system and was deposited at 1175°C for 7.6 hours to obtain the silicon-oxygen material matrix. Simultaneously, 30g of tin metal was added to heating chamber 2, where the vacuum was evacuated to below 10Pa and heating began to 1100°C. 30g of boron was added to heating chamber 3, where the vacuum was evacuated to below 10Pa and heating began to 1180°C. The vapor in chambers 2 and 3 entered the deposition system, where deposition was carried out at 850°C for 6.9 hours. After cooling naturally to room temperature, the deposited material was formed into a bulk form.
[0288] Example 18
[0289] 900g of Si powder was mixed with 1200g of SiO2 powder with a grain size of 2nm to create a silicon source. This was then placed in the first chamber of a vacuum furnace, where the vacuum was evacuated to below 1Pa and heating began. After heating to 1300°C, the material entered the deposition system and was deposited at 1175°C for 7.5 hours to obtain the silicon-oxygen material matrix. Simultaneously, 30g of tin metal was added to the second chamber, where the vacuum was evacuated to below 10Pa and heating began to 1100°C. 30g of lithium was added to the third chamber, where the vacuum was evacuated to below 10Pa and heating began to 900°C. The vapor in chambers 2 and 3 entered the deposition system, where deposition was carried out at 855°C for 7 hours. After cooling naturally to room temperature, the deposited material formed into a bulk form.
[0290] The preparation parameters in Comparative Examples 1-3 are basically the same as those in Example 1. The specific parameters are shown in Table 1. Specifically,
[0291] Comparative Example 1
[0292] A silicon source was obtained by mixing 900 g of Si powder with 1200 g of SiO2 powder with a grain size of 2 nm. The mixture was added to the heating chamber 1 of a vacuum furnace, the vacuum was evacuated to below 1 Pa, and heating was started to 1300°C. The vapor in the heating chamber 1 entered the deposition zone in the deposition system, and the temperature of the deposition zone was controlled to be maintained at 1170°C. The deposition time was 7.3 h, and the bulk deposition material was obtained after natural cooling to room temperature.
[0293] Comparative Example 2
[0294] 900g of Si powder was mixed with 1200g of SiO2 powder with a grain size of 2nm to obtain a silicon source, which was added to the heating chamber 1 of a vacuum furnace, and the vacuum was evacuated to below 1Pa and heating began. After heating to 1300℃, it entered the deposition system and was deposited at 1170℃ for 7.6h to obtain a silicon oxide material matrix. At the same time, 30g of boron was added to the heating chamber 2, and then the vacuum was evacuated to below 10Pa and heating began. After heating to 1100℃, it entered the deposition system and was deposited at 800℃ for 7.4h. After naturally cooling to room temperature, a bulk deposition material was obtained.
[0295] The obtained deposited material was crushed into particles with a median particle size of 5 μm by air flow milling, and added to a CVD vapor deposition furnace for carbon coating treatment. Acetylene gas was introduced at a mass flow rate of 700 sccm and deposited at 680°C for 5 hours. The coated material was placed under nitrogen protection and heated to 800°C at a heating rate of 5°C / min and kept at that temperature for 1 hour. After natural cooling, a silicon-oxygen composite material was obtained.
[0296] Comparative Example 3
[0297] 900g of Si powder was mixed with 1200g of SiO2 powder with a grain size of 2nm to obtain a silicon source, which was added to the heating chamber 1 of a vacuum furnace, and the vacuum was evacuated to below 1Pa and heating began. After heating to 1300℃, it entered the deposition system and was deposited at 1180℃ for 7.5h to obtain a silicon oxide material matrix; 30g of tin metal was added to the heating chamber 2, and then the vacuum was evacuated to below 10Pa and heating began. After heating to 1100℃, it entered the deposition system and was deposited at 800℃ for 7.5h. After naturally cooling to room temperature, a block-shaped deposition material was obtained.
[0298] The obtained deposited material was crushed into particles with a median particle size of 5 μm by air flow milling, and added to a CVD vapor deposition furnace for carbon coating treatment. Acetylene gas was introduced at a mass flow rate of 700 sccm and deposited at 800°C for 5 hours. The coated material was placed under nitrogen protection and heated to 800°C at a heating rate of 5°C / min and kept at that temperature for 1 hour. After natural cooling, a silicon-oxygen composite material was obtained.
[0299] 2. Test Method
[0300] 1. Lithium ion diffusion coefficient of each element
[0301] (1) Preparation of button cell: Mix the single material formed by each doping element or silicon element, binder, and conductive agent in a ratio of 8:1:1 and add them to deionized water, mix and stir evenly to obtain negative electrode slurry; apply the negative electrode slurry on one surface of the negative electrode current collector copper foil, dry, cold press, and cut to obtain negative electrode sheets, and use a punching die to obtain a certain area (this application uses 153.86mm 2 ) negative electrode disc. A metallic lithium sheet was used as the counter electrode, a PP film was used as the separator, and the electrolyte formulation was: ethylene carbonate, ethyl methyl carbonate, diethyl carbonate, and FEC were mixed in a volume ratio of 1:1:1:1 to form a solvent. LiPF6 was dissolved in the solvent as the lithium salt to prepare a solution with a concentration of 1 mol / L. The cells were assembled into CR2032 button cells in an argon-protected glove box.
[0302] (2) The lithium ion diffusion coefficient of the simple substance formed by the doping element or the simple substance of silicon is calculated according to the following formula: D Li =1 / (1000×S×Z iq ),
[0303] Where: D Li is the lithium ion diffusion coefficient; S is the area of the small disc in the button battery prepared above; Z iq is the specific capacity of the single material;
[0304] Among them, Z iq The following test steps can be used: at 25 ° C, use a 0.1C current to charge the button battery prepared above at a constant current until the battery voltage is less than 0.05V, and then let it stand for 120 minutes; then use a 0.1C current to discharge the button battery prepared above at a constant current until the battery voltage is greater than 1.5V, and measure the specific capacity of the button battery at this time and record it as Z iq .
[0305] 2. Confirm the existence form of the first doping element
[0306] X-ray diffraction (XRD) was used to confirm the presence of the first doping element: the silicon-oxygen composite material was tested using an X-ray powder diffractometer (XRD, instrument model: Bruker D8 ADVANCE), with a Cu Kα target; the voltage and current were 40 kV / 40 mA, the scanning angle range was 5° to 80°, the scanning step length was 0.00836°, and the time per step was 0.3 s. The morphology of the diffraction peak in the obtained spectrum determined that the first doping element existed in crystalline form.
[0307] 3. Uniform doping of the first doping element
[0308] Conductive adhesive was applied to the sample stage. Powdered samples of the silicon-oxygen composite materials from each example and comparative example were spread flat on the adhesive. Unattached powder was blown away with an ear bulb. The sample was then sprayed with gold. The powdered samples were then cross-sectioned using argon plasma. Scanning electron micrographs of the powdered samples were obtained using a Philips XL-30 field-emission scanning electron microscope equipped with an EDS at an accelerating voltage of 10 kV and an emission current of 10 mA.
[0309] 4. Crystal grain size formed by the first doping element
[0310] The XRD pattern of the silicon-oxygen composite material was tested according to the JIS / K0131-1996 test standard. Based on the XRD pattern of the silicon-oxygen composite material, the half-height width β and the diffraction angle θ of the (101) crystal plane diffraction peak of the first doping element were taken and substituted into the Debye-Scherrer formula to calculate the crystal grain size. The Debye-Scherrer formula is as follows: Dhkl = kλ / (βcosθ), where Dhkl represents the crystal grain size in nm; k represents the Scherrer constant, 0.89; λ represents the wavelength of the incident X-ray, 0.15406 nm; β represents the half-height width of the diffraction peak, in rad; and θ represents the diffraction angle in degrees.
[0311] 5. Silicon grain size
[0312] The XRD pattern of the silicon-oxygen composite material was tested according to the JIS / K0131-1996 test standard. Based on the XRD pattern of the silicon-oxygen composite material, the half-height width β and the diffraction angle θ of the Si(111) crystal plane diffraction peak were taken and substituted into the Debye-Scherrer formula to calculate the grain size of the silicon grains. The Debye-Scherrer formula is as follows: Dhkl = kλ / (βcosθ), where Dhkl represents the grain size of the silicon grain in nm; k represents the Scherrer constant, 0.89; λ represents the wavelength of the incident X-ray, 0.15406 nm; β represents the half-height width of the diffraction peak in rad; and θ represents the diffraction angle in degrees.
[0313] 6. Mass content of the first doping element and the second doping element
[0314] The determination is performed with reference to the EPA 6010D-2014 standard; specifically, ICP-OES (elemental analysis-inductively coupled plasma optical emission spectrometry) testing can be used. The sample to be tested is first dissolved into a liquid with a strong acid, and then the liquid is introduced into an ICP light source by atomization. The gaseous atoms to be tested are further ionized and excited in a strong magnetic field, and then restored to the ground state from the excited state. In the above process, energy is released and recorded as different characteristic spectral lines, and quantitative analysis of the first doping element and the second doping element is performed.
[0315] 7. Battery 25℃ cycle performance test
[0316] The secondary batteries prepared in each example and comparative example were charged at a constant current rate of 0.5C to a charge cutoff voltage of 4.25V, then charged at a constant voltage rate to a current of ≤0.05C, allowed to rest for 5 minutes, and then discharged at a constant current rate of 0.33C to a discharge cutoff voltage of 2V, allowed to rest for 5 minutes. This constituted one charge-discharge cycle. The batteries were subjected to cyclic charge-discharge testing using this method until the battery capacity decayed to 80%. The number of cycles at this point is the battery's cycle life at 25°C.
[0317] 8. Battery energy density
[0318] At 25°C, the secondary batteries prepared in each example and comparative example were allowed to rest for 2 hours. After charging the secondary batteries at 0.1C to the charge cutoff voltage, constant voltage charging was continued at the charge cutoff voltage until the current reached 0.05C, at which point charging was terminated (where C represents the rated capacity of the battery cell). The secondary batteries were allowed to rest at 25°C for 1 hour. Then, they were discharged at 0.1C to the discharge cutoff voltage. The total discharge capacity (C0) of the secondary batteries was recorded, and the total discharge energy (E0) was recorded.
[0319] Secondary battery mass measurement: Place the secondary battery on an electronic balance until the mass is stable, and read the mass value M0 of the secondary battery.
[0320] Secondary battery mass energy density = E0 / M0.
[0321] 9. Battery 40% SOC discharge time
[0322] The secondary batteries prepared in the examples and comparative examples were discharged at a constant current of 0.33C to 2.8V and allowed to stand for 30 min; charged at a constant current of 0.33C to 4.25V and then at a constant voltage of 0.05C until the voltage stabilized, and allowed to stand for 30 min; discharged at a constant current of 0.33C to 2.8V, at which time the initial capacity C0 was read, and allowed to stand for 30 min; charged at a constant current of 0.33C to 4.25V and then at a constant voltage of 0.05C until the voltage stabilized, and allowed to stand for 30 min; discharged at a constant current of 0.33C to 0.4C0Ah (40%) SOC and allowed to stand for 60 min; discharged at a constant current of 4.5C to 2.8V, and the discharge time was recorded.
[0323] 10. Battery low temperature discharge capacity retention rate
[0324] At -20°C, the secondary batteries prepared in the above examples and comparative examples were charged at a constant current of 0.33C to a voltage of 4.25V. They were then charged at a constant voltage of 4.25V to a current of ≤0.05C. The batteries were then discharged at a constant current of 0.33C to a voltage of 2.5V. This constituted one charge-discharge cycle, and the discharge capacity (C1) of the first cycle was recorded. This charge and discharge cycle was repeated, and the discharge capacity (C2) after 500 cycles was recorded.
[0325] The capacity retention rate of the battery after 500 cycles = C2 / C1×100%.
[0326] 3. Analysis of test results of various embodiments and comparative examples
[0327] The silicon-oxygen composite materials, negative electrode sheets and batteries of the embodiments and comparative examples were prepared according to the above methods, and various parameters were measured. The results are shown in Tables 1, 2, 3 and 4 below.
[0328] Table 1
[0329] Table 2
[0330] Table 3
[0331] Table 4
[0332] FIG1 is an XRD diagram of the silicon-oxygen composite material of Example 1. As can be seen from the XRD diagram of FIG1 , a peak appears at a position where 2θ is 33°, indicating that the tin in Example 1 exists in the silicon-oxygen material matrix in the form of crystals.
[0333] FIG2 is a scanning electron microscope image of the silicon-oxygen composite material, from which it can be seen that the first doping element tin is uniformly distributed in the silicon-oxygen material matrix.
[0334] The silicon-oxygen composite material in Examples 1-18 comprises a silicon-oxygen material matrix and a first doping element of at least one of Sn, Ge, Sb, and Bi distributed in the silicon-oxygen material matrix, wherein the lithium ion diffusion coefficient of the Sn, Ge, Sb, and Bi elemental substances at 25°C is greater than the lithium ion diffusion coefficient of the silicon elemental substance at 25°C, at least part of the Sn, Ge, Sb, or Bi exists in a crystalline form in the silicon-oxygen material matrix, and the grain size of the first doping element is ≤9nm.
[0335] From the comparison of Examples 1-18 and Comparative Example 1, it can be seen that the silicon-oxygen composite material contains a first doping element of Sn, Ge, Sb or Bi, which can extend the discharge time of the battery, improve the rate performance of the battery, improve the cycle performance of the battery, and extend the cycle life of the battery.
[0336] From the comparison of Examples 1-18 and Comparative Example 2, it can be seen that the lithium ion diffusion coefficient of the first doping element in the silicon-oxygen composite material is greater than the lithium ion diffusion coefficient of the silicon element, which can extend the discharge time of the battery, improve the battery's rate performance, improve the battery's cycle performance, and extend the battery's cycle life.
[0337] From the comparison of Examples 1-16 and Comparative Example 3, it can be seen that the grain size of the crystals formed by the first doping element in the silicon-oxygen composite material is ≤9nm, which can extend the discharge time of the battery, improve the battery's rate performance, improve the battery's cycle performance, and extend the battery's cycle life.
[0338] From the comparison between Examples 1 and 6 and Example 7, it can be seen that the grain size of the crystals formed by the first doping element is ≤7nm, which can further extend the discharge time of the battery, further improve the rate performance and cycle performance of the battery, and extend the cycle life of the battery.
[0339] As can be seen from Examples 1-16, the grain size Y nm of the crystals in the silicon-oxygen composite material and the grain size X nm of the silicon grains satisfy at least one of the following relationships: 0.35≤Y / 2X≤4 or -5≤5Xsin2θ-Y≤15, where 2θ is the XRD diffraction angle of the crystals formed by the doping element. The battery has excellent cycle performance and rate performance, and the battery has a long cycle life.
[0340] From the comparison of Examples 1-4, 6-8, 10-11 with Example 9, it can be seen that the grain size of the crystals in the silicon-oxygen composite material and the grain size X nm of the silicon grains satisfy the following relationship: 0.7≤Y / 2X≤4, which can further improve the cycle performance of the battery.
[0341] From the comparison of Examples 1-4, 6-8, 10-11 with Example 9, it can be seen that the grain size of the crystals in the silicon-oxygen composite material and the grain size X nm of the silicon grains satisfy the following relationship: -5≤5Xsin2θ-Y≤10, where 2θ is the XRD diffraction angle of the tin crystal, which can further improve the cycle performance of the battery.
[0342] As can be seen from Examples 1-16, the XRD diffraction pattern of the silicon-oxygen composite material contains a diffraction peak of the first doping element crystal, the half-peak width of the diffraction peak of the first doping element crystal is 3°-7°, and the diffraction peak intensity of the crystal is 600S. -1 -1200S -1 , the battery has excellent cycle performance and rate performance, and the battery has a long cycle life.
[0343] As can be seen from Examples 1-16, when the mass fraction of the first doping element is less than or equal to 12% based on the total mass of the silicon-oxygen composite material, the battery exhibits excellent cycle performance and rate performance, and has a long cycle life. A comparison of Examples 1 and 12-14 with Examples 15-16 shows that when the mass fraction of the first doping element is 1%-10% based on the total mass of the silicon-oxygen composite material, the battery's discharge time can be further extended and its rate performance can be further improved.
[0344] The silicon-oxygen composite materials of Examples 17 and 18 also include a second doping element of boron or lithium. A comparison of Example 17 with Example 1 shows that doping with the second element, boron, can increase the battery's discharge capacity retention at low temperatures, improving the battery's performance at low temperatures. A comparison of Example 18 with Example 1 shows that doping with the second element, lithium, can increase the battery's energy density, meeting the requirements of new battery technologies.
[0345] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A silicon-oxygen composite material, It is characterized in that A silicon-oxygen material matrix and a first doping element distributed in the silicon-oxygen material matrix, wherein at least a portion of the first doping element exists in the silicon-oxygen material matrix in a crystalline form, and a grain size of the first doping element is ≤9 nm, wherein the first doping element satisfies: a lithium ion diffusion coefficient of a single substance of the first doping element at 25° C. is greater than a lithium ion diffusion coefficient of a single substance of silicon at 25° C.
2. The silicon-oxygen composite material according to claim 1, It is characterized in that The lithium ion diffusion coefficient of the first doping element at 25°C is greater than 10 - 14 cm 2 / S, can be greater than 10 -14 cm 2 / S and less than or equal to 10 -13 cm 2 / S; and / or, The lithium ion diffusion coefficient of the silicon element at 25°C is less than 10 -14 cm 2 / S, can be greater than 10 -15 cm 2 / S and less than 10 -14 cm 2 / S.
3. The silicon-oxygen composite material according to claim 1 or 2, It is characterized in that The first doping element includes at least one of Sn, Ge, Sb, Bi, and Sr.
4. The silicon-oxygen composite material according to any one of claims 1 to 3, It is characterized in that The grain size of the first doping element is ≤7nm.
5. The silicon-oxygen composite material according to any one of claims 1 to 4, It is characterized in that The XRD diffraction spectrum of the silicon-oxygen composite material also includes diffraction peaks of silicon grains, and the silicon-oxygen composite material has at least one of the following relations (1)-(2): (1) 0.35≤Y / 2X≤4, optionally, 0.7≤Y / 2X≤4; (2) -5≤5Xsin2θ-Y≤15, optionally, -5≤5Xsin2θ-Y≤10; Wherein, Y is the grain size of the first doping element, X is the grain size of the silicon grains, the units of X and Y are both nm, and 2θ is the XRD diffraction angle of the crystal.
6. The silicon-oxygen composite material according to any one of claims 1 to 5, It is characterized in that The XRD diffraction spectrum of the silicon-oxygen composite material contains a diffraction peak of the first doping element crystal, and the half-peak width of the diffraction peak of the first doping element crystal is 3°-7°; and / or the diffraction peak intensity of the crystal is 600S -1 -1200S -1 .
7. The silicon-oxygen composite material according to any one of claims 1 to 6, It is characterized in that Based on the total mass of the silicon-oxygen composite material, the mass fraction of the first doping element is less than or equal to 12%, and can be optionally 1%-10%.
8. The silicon-oxygen composite material according to any one of claims 1 to 7, It is characterized in that The silicon-oxygen composite material further includes a second doping element, wherein the second doping element includes at least one of a non-metallic element, an alkali metal element, and an alkaline earth metal element; Optionally, the non-metallic element includes at least one of B, N, F, Cl, and S; Optionally, the alkali metal element includes at least one of Li, Na, and K; Optionally, the alkaline earth metal element includes at least one of Mg, Ca, Be, and Sr.
9. The silicon-oxygen composite material according to claim 8, It is characterized in that Based on the total mass of the silicon-oxygen composite material, the mass fraction of the second doping element is less than or equal to 7%, and may be 1%-5%.
10. The silicon-oxygen composite material according to any one of claims 1 to 9, It is characterized in that The silicon-oxygen composite material further includes a carbon layer at least partially covering the surface of the silicon-oxygen material matrix; optionally, the carbon layer has a thickness of 1-4 nm.
11. The silicon-oxygen composite material according to any one of claims 1 to 10, It is characterized in that The volume distribution particle size Dv50 of the silicon-oxygen composite material is 3 μm-8 μm, and can be optionally 4 μm-6 μm.
12. A method for preparing a silicon-oxygen composite material, It is characterized in that The preparation method comprises: Performing a first vapor deposition including silicon and silicon dioxide to obtain a silicon-oxygen material matrix; A second vapor containing a first doping element is subjected to a second vapor deposition on the silicon-oxygen material matrix to obtain the silicon-oxygen composite material, wherein at least a portion of the first doping element exists in the silicon-oxygen material matrix in the form of crystals, and the grain size of the first doping element crystals is ≤9nm, wherein the first doping element satisfies: the lithium ion diffusion coefficient of the first doping element at 25°C is greater than the lithium ion diffusion coefficient of silicon at 25°C.
13. The preparation method according to claim 12, It is characterized in that The temperature of the first vapor deposition is 1000° C.-1300° C., and may be 1100° C.-1250° C.; and / or, the time of the first vapor deposition is 6 h-12 h, and may be 8 h-10 h.
14. The preparation method according to claim 12 or 13, It is characterized in that The temperature of the second vapor deposition is 800° C.-900° C., and can be 820° C.-880° C.; and / or, the time of the second vapor deposition is 4 h-10 h, and can be 6 h-8 h.
15. The preparation method according to any one of claims 12 to 14, It is characterized in that The preparation method comprises: Performing a second vapor deposition on the silicon-oxygen material matrix with a second vapor containing a first doping element and a second doping element to obtain the silicon-oxygen composite material, wherein the second doping element includes at least one of a non-metallic element, an alkali metal element, and an alkaline earth metal element; Optionally, the non-metallic element includes at least one of B, N, F, Cl, and S; Optionally, the alkali metal element includes at least one of Li, Na, and K; Optionally, the alkaline earth metal element includes at least one of Mg, Ca, Be, and Sr.
16. The preparation method according to any one of claims 12 to 15, It is characterized in that The preparation method further comprises: performing carbon coating treatment on the surface of the silicon-oxygen composite material; Optionally, the temperature of the carbon coating treatment is 500°C-750°C, optionally 660°C-720°C; Optionally, the carbon coating treatment time is 2h-10h, optionally 6h-8h.
17. A secondary battery comprising a negative electrode plate, It is characterized in that The negative electrode plate includes a negative electrode active material, and the negative electrode active material includes the silicon-oxygen composite material according to any one of claims 1 to 11 or the silicon-oxygen composite material prepared by the preparation method according to any one of claims 12 to 16.
18. An electrical device, It is characterized in that A secondary battery comprising the secondary battery according to claim 17.
Citation Information
Patent Citations
High-nickel material coated with aluminum and lithium silicate on surface and doped with fluorine on surface layer and preparation method
CN108807931A
Lithium ion battery silicon-based composite negative electrode material and preparation method thereof
CN113506861A
Storage System, Storage Device, and Operating Method Therefor
KR1020210124687A
Negative electrode active substance and production method thereof, battery, and electronic device
WO2019031516A1
Cited By
Solar cell and preparation method thereof, laminated cell, photovoltaic module and processing equipment
CN121985623A